ANALISIS MISKONSEPSI SISWA PADA KONSEP PENYERAPAN NUTRISI MENGGUNAKAN MEDIA VISUAL TIGA DIMENSI - Cahyaningsih, Andini Tri; Angger Wardhani, Prayuningtyas; Fahrurrozi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze student misconceptions in the concept of nutrient absorption in the digestive system among Grade V students at SDN Sumberjaya 02, Tambun Selatan, and to examine the need for three-dimensional (3D) visual media as a remedial learning tool. This research employs a needs analysis approach within a Research and Development (R&D) framework. Data were collected from 22 students using a diagnostic test combined with the Certainty of Response Index (CRI), supported by a questionnaire administered to 7 students and structured teacher and student interviews. Results indicate that 59.1% of students hold a serious misconception regarding the organ of nutrient absorption, and 54.5% misconceive the digestive process of carbohydrates. CRI analysis identified that 72.7% of students experienced minor to moderate misconceptions. Questionnaire results reveal 100% agreement toward 3D model use in learning. Student interviews revealed a critical kinesthetic gap: all students expressed a desire not only to see but to physically touch and hold 3D organ models, an experience never provided, as learning was conducted solely through smartboard video viewing without group project activities. Teacher interviews uncovered an access-utility paradox: a 3D human organ model was already available in the school inventory but had never been used due to accessibility barriers. These findings provide an empirical foundation for developing portable, hands-on 3D visual media specifically targeting misconceptions in nutrient absorption at the elementary school level.